Etika dan Profesionalitas Konselor Kristen pada Konflik Keluarga - Alisaid Prawiro Negara; Bobby Kurnia Putrawan; Sutrisno Sutrisno; Susanti Embong Bulan (LP2M Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
Counseling crisis is experienced by many people because of a lack of trust in Christian counselors. One of the current arguments is that the counselor is not an expert or a graduate in the field of counseling study. Not to mention the moral problems the counselor shows to the person being served, both in speech and even to the point where someone commits sexual harassment. From this, the lack of trust in counselors occurs, even though many families need the help of a counselor with their family problems, such as divorce. This study uses the method used is a literature review. Literature reviews discuss published information in a particular field of research and sometimes knowledge in a specific study area over a certain period. The results of this study are, first, Christian counseling services as a representative of the Lord Jesus Christ. Second, there is special attention to church pastors. Third, the right solution amid increasingly complex changes and developments. Fourth, it is implemented proactively. Fifth, good cooperation between the church (the pastor and workers) and the entire congregation, especially husband and wife.